Oral administration of melatonin increased superoxide dismutase and reduced malondialdehyde in male wistar rats (rattus norvegicus) induced by cigarette smoke - Aprilany Stella peng; Wimpie Pangkahila; I Wayan Weta (IJAAM (Indonesian Journal of Anti-Aging Medicine), 2020)
Introduction: Cigarette smoke is one of the most common sources of free radicals that accelerate aging process. This process can be countered by avoiding cigarette and consuming anti-oxidants. Melatonin is one of well-known anti-oxidant which can be safely consumed. Therefore, the aim of this study was to assess the effect of oral melatonin supplementation toward the level of superoxide dismutase and malondialdehyde in male Wistar rats exposed by cigarette smoke. Methods: An experimental pretest-posttest control group study was conducted using 18 male Wistar rats, 12 weeks old, and 180-200 gr in weight. The subjects were divided into two groups (n= 9 rats) randomly. Both groups were exposed by cigarette smoke but treatment group (P1) was treated with 2 mg of melatonin per 200 gr BW rats for 14 days. The levels of SOD and MDA were measured using the ELISA method. Results: The baseline level of SOD and MDA in both groups was homogenous. At the end of the experiment, there was significant increase of SOD level (baseline: 1.13±0.45; post-treatment: 2.57±0.08 ng/mL; p= <0.001) and decreased in MDA level (baseline: 9.53 ± 1.25; post-treatment: 1.44 ± 0.46; p= <0.001) in treatment group while no change was observed in both SOD and MDA in control group. Conclusion: The oral consumption of melatonin countered the adverse effect of smoking by increasing the level of SOD and lowers MDA level.